Peran Jalur Phosphatidyl-Inositol-3-kinase (PI3K) dalam Resistensi Kemoterapi pada Kanker - Zanuar Abidin (Universitas Muhammadiyah Surabaya, 2018)
Cancer has the ability to develop resistance to chemotherapy and increased prevalence of this drug-resistant cancer requires further research and development of treatment. There are several mechanisms that can stimulate chemotherapy resistance, such as drug inactivation, drug effectiveness mechanism, HER2 role, PI3K pathway, DNA damage repair, and apoptotic inhibition. The PI3K pathway is an important signal transduction pathway in the growth and development of cancer. This pathway plays a role in several functions, such as proliferation, cell growth, and tumor survival. PI3K activation has been identified in some cases of cancer, including breast cancer. This pathway undergoes excessive activation resulting in resistance to chemotherapy and increased metastasis.